2003
DOI: 10.1007/pl00021501
|View full text |Cite
|
Sign up to set email alerts
|

Patchiness of River–Groundwater Interactions within Two Floodplain Landscapes and Diversity of Aquatic Invertebrate Communities

Abstract: In fluvial systems, the interactions between rivers and groundwater significantly affect various ecological structures (for example, riparian vegetation) and functions. To examine the effects of hydrological exchange between groundwater and surface water on the distribution of aquatic invertebrates within a riverine landscape, we investigated the main stem, tributaries, and various surface and subsurface waters of two floodplains of a southern Alpine river (Brenno, Switzerland) in terms of their physicochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Differential patterns of surface-and groundwater exchanges produce a mosaic of 'shifting subsurface flow paths'. The importance of differential hydrologic exchange for biodiversity distributions has been demonstrated by Brunke et al (2003) by comparing different intermountain floodplains in southern Switzerland. Harner and Stanford (2003) found that cottonwood trees grew faster and had lower C:N in their leaves in zones of groundwater upwelling than downwelling zones on the same flood plain and suggested that the observed differences in riparian canopy trees could influence distribution and abundance of leaf herbivores.…”
Section: Floodplain Biodiversitymentioning
confidence: 99%
“…Differential patterns of surface-and groundwater exchanges produce a mosaic of 'shifting subsurface flow paths'. The importance of differential hydrologic exchange for biodiversity distributions has been demonstrated by Brunke et al (2003) by comparing different intermountain floodplains in southern Switzerland. Harner and Stanford (2003) found that cottonwood trees grew faster and had lower C:N in their leaves in zones of groundwater upwelling than downwelling zones on the same flood plain and suggested that the observed differences in riparian canopy trees could influence distribution and abundance of leaf herbivores.…”
Section: Floodplain Biodiversitymentioning
confidence: 99%
“…Since the formulation of the patch dynamics concept (Townsend, 1989), lotic ecologists and biogeochemists have developed an increased interest in these dynamics and the heterogeneity of hyporheic flows (Hendricks, 1993;Stanley et al, 1997;Lake, 2000;Brunke et al, 2003). Whereas patchiness makes hyporheic research difficult (Palmer, 1993), ecologists mostly identify such complexity as an enhancer of biogeochemical processes, e.g.…”
Section: Hyporheic Flow Variability In Previous Workmentioning
confidence: 99%
“…The rapidly developing interest in using traits to understand ecological responses to disturbances (Schmera, Podani, Heino, Erős, & Poff, ) could be extended to GDEs. In more hydrologically dynamic GDEs, species with traits such as sensitivity to desiccation or poor dispersal ability may be vulnerable to groundwater regime alteration and therefore make especially effective ecological indicators (Brunke, Hoehn, & Gonser, ; de Szoeke, Crisman, & Thurman, ; Stumpp & Hose, ). Poor dispersers may lack the mobility to track favourable hydrological conditions and be restricted to hydrologically stable streams with groundwater regimes that buffer against precipitation variability (Kath et al, ).…”
Section: The Five Steps Of Fergramentioning
confidence: 99%
“…The third step in FERGRA is to determine GDE–groundwater connectivity to assess the hydrogeological association of altered groundwater regimes with ecological responses by multiple GDEs in the landscape. The importance of groundwater connectivity for the persistence and functioning of the different classes of GDEs (Table , Figure ) is demonstrated by changes in the habitat and condition of riparian vegetation (Eamus et al, ), fish (Falke et al, ), macroinvertebrate (Brunke et al, ), and stygofauna (Stumpp & Hose, ) communities when groundwater connectivity is altered. Within FERGRA, we hypothesize that alterations to GDE–groundwater connectivity are the primary ecohydrological mechanism by which groundwater regime alterations elicit ecological responses in all classes of GDEs.…”
Section: The Five Steps Of Fergramentioning
confidence: 99%